Internet of Things (IoT) Technology in Smart Homes: Vitalizing Human-Computer Interaction - Rini, Sanjeev Kumar Sharma (Mathematical Statistician and Engineering Applications, 2023)
Internet of Things (IoT) as a novel technology has transformed the consumer market. IoT technology enabled smart homeshas provided convenience and effortless living to consumers through its technologically creative offerings. Extensive focus on IoT products has been the mainstream, while the domain of “smart” homes with embedded IoT technology has been less explored. Moreover, such studies have been confined to the Western and developed regions, and less focus has been on emerging markets.The aim of this paper is to systematically review the smart home literature and survey the current state of play from the users’ perspective. The review presents a comprehensive view of smart home definitions and characteristics. Then the study precisely discusses about of the smart home types, related services and benefits. After outlining the smart home benefits, the review discusses the challenges and barriers to smart home implementation. This review concludes by providing suggestions for future research. Additionally, the review contributes theoretically to the growing body of research on IoT adoption along with practical implications for marketers from the Indian consumer’s perspective.